Design And Development Of Adaptive Spatial Filters For Reduction Of Gaussian And Impulse Noise In Images - Kam, Yvonne Hwei Syn (2008)
Noise is an undesirable artefact of images, which should be removed or reduced without significantly changing the features and details of the original image. This can be achieved by means of adaptive filtering. This, the goal of this research is to design and develop a new set of adaptive filters in the spatial domain to reduce Gaussian and impulse noise in greyscale images.